Consumer Preference for Mocaf Packaging using Analytical Hierarchy Process (AHP) - Wandhansari Sekar Jatiningrum; Fatma Hermining Astuti; Choirul Sayid Sabiq; Arma Ludfy Andika; Luthfi Bagus Adityo; Hasan Mastrisiswadi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
Wheat flour consumption in Indonesia continues to increase, so the government must import wheat on a large scale. One of the ways to reduce wheat consumption is by using substitutes. Mocaf (modified cassava flour) is a kind of flour that derived from cassava plants (Manihot esculenta). This flour can be used as a substitute for wheat flour due to its similar characteristics. Even though it has high economic potential, mocaf has only been marketed locally. One of the reason is the lack of quality packaging. The purpose of this study is to identify consumer preferences for mocaf packaging so that they can market the product not only locally but also nationally. In this study, AHP (Analytical Hierarchy Process) method with four alternatives (plastic stand up pouch combination, Aluminium foil stand up pouch combination, screen printing plastic pouch, and paper pouch combination) and three criteria (price, model, and durability) is used to determine consumer preferences for mocaf packaging. This research obtained the conclusion that the highest weight for criterion and alternative are price and the screen printing plastic pouch.